Search for a structure in the B0sπ± invariant mass spectrum with the ATLAS experiment - Aaboud, Morad; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Britzger, Daniel; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physical review letters, 2018)
A search for the narrow structure, X(5568), reported by the D0 Collaboration in the decay sequence X→B0sπ±, B0s→J/ψϕ, is presented. The analysis is based on a data sample recorded with the ATLAS detector at the LHC corresponding to 4.9 fb−1 of pp collisions at 7 TeV and 19.5 fb−1 at 8 TeV. No significant signal was found. Upper limits on the number of signal events, with properties corresponding to those reported by D0, and on the X production rate relative to B0s mesons, ρX, were determined at 95% confidence level. The results are N(X)<382 and ρX<0.015 for B0s mesons with transverse momenta above 10 GeV, and N(X)<356 and ρX<0.016 for transverse momenta above 15 GeV. Limits are also set for potential B0sπ± resonances in the mass range 5550 to 5700 MeV.
Im Titel wird "pi" als griechischer Buchstabe dargestellt
Im Titel sind "0" und "s" untereinander geschrieben: "0" hoch-, "s" tiefgestellt
Im Titel sind "+" und "-" untereinander geschrieben: "+" hochgestellt, "-" tiefgestellt
M. Aaboud, A.E. Bolz, A.E. Baas, O. Brandt, D. Britzger, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, H. Meyer Zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S.M. Weber, M. Wessels [und weitere] (ATLAS Collaboration)
Gesehen am 08.04.2019